Perspektif Tri Hita Karana Dan Tattwam Asi Pada Aksesibilitas Pimpinan Dengan Moderasi Beragama Sebagai Variabel Intervening - I Made Ardika Yasa; I Gede Ratnaya (Jayapangus Press, 2022)
The leader must plan, implement and maintain the organization's management with full professional responsibility based on competence. As a manager, spiritual capital derived from the value of local wisdom and religious moderation becomes a new perspective that a leader must internalize. This study analyzes whether Tri Hita Karana, Tattwam Asi, and religious moderation directly affect Leadership Accessibility and whether Tri Hita Karana and Tattwam Asi indirectly affect Leadership Accessibility with religious moderation as a mediation variable. This research was conducted in Mataram City, with respondents being leaders in private or public organizations sectors. This study used a questionnaire instrument as a data collection method. Data analysis in this study used Partial Least Square (PLS) 23.0 analysis. This study obtained the results that Tri Hita Karana had a significant positive effect on religious moderation but had no effect on Leader Accessibility directly, and Tattwam Asi had a significant positive effect on religious moderation but had no effect on leader accessibility directly. In contrast, direct religious moderation significantly positively affected Leadership Accessibility. For indirect influence, Tri Hita Karana and Tattwa Asi have complete mediation on Leadership Accessibility with religious moderation as an intervening variable. The results of this study contribute to supporting role theory and providing an understanding of the influence of the leader's spiritual capital from the perspective of Tri Hita Karana and the teachings of Tattwam Asi. Leaders are expected to use a sound mind to carry out management planning, coaching with appropriate actions according to the code of ethics, and correct delivery of performance evaluation results without being separated from the independence and professionalism of the leader.